Afectación de las ventas en la empresa HABITAR INMOBILIARIA S.A, a causa del covid19 en relación con el periodo 2019-2020 - Morejón Barragán, Jean Carlos (2021)
This case study was carried out with the objective of analyzing the financial situation of the company “Inmobiliaria Habitar SA” in the province of Tungurahua, in times of pandemic, in this research the following methodology was used: descriptive and analytical analysis, Through which information was obtained through a virtual interview with the manager and the accountant in charge of the Accounting Department that served as the basis for carrying out the present study. The objective of the company is to provide all people with a high quality service to acquire properties in optimal conditions, guaranteeing the buyer houses, land or buildings at the best prices in the Real Estate market. As a result, the respective vertical and horizontal analysis was obtained, it was possible to identify that the sales of the company Habitar Inmobiliaria decreased in the course of 2020, that is, sales income was reduced by -11.54% in monetary terms, the decrease is of -15069.65, unlike the sales of the year 2019, continuing with the analysis it can be seen that the expenses in the aforementioned year increased by 23.93% which in turn generates a decrease in the profits in a -37.58% that is, in monetary terms $ -14025.92. The main conclusion was regarding the economic variables, it can be concluded that this real estate sector continues to be very productive and that it generates important contributions to the country's GDP, which is viable.